Effect of Profitability on the Stock Price of Luxury Goods Retail Companies in the Retailing Industry from Stock Market in Saudi Arabia (The International Journal for Scientific Research, 2024)
The purpose of this study is to analyze profitability by using the return on assets, return on equity and a net profit margin and know their effect on the stock price in order to know the relationship between profitability and the stock price. This study uses secondary data. The sample used are six luxury goods retailers companies in the retail industry from Stock Market in Saudi Arabia for the period from 2015 to 2019. Samples in this study were taken using purposive sampling technique. The data was collected from the index of the stock market in KSA (The Tadawul All Share Index "TASI"). Independent variables in this study are the return on assets (ROA), the return on equity (ROE) and the net profit margin (NPM). The dependent variable is the stock price (SP). Multiple linear regression analysis was used to test hypotheses in this study. EViews program was used to calculate the multiple linear regression. It has been confirmed that the data is suitable for conducting a multiple linear regression analysis, and this was done by test the unit root by using ADF and PP techniques on the time series of this study, and examining multicollinearity test, heteroscedasticity test and normality test. The results of the multiple linear regression analysis showed that the (ROA) partially has a significant positive effect on the stock price, and that the (ROE) partially has a positive but not significant effect on the stock price, and that the (NPM) partially has a significant negative effect on the stock price, and that the three profitability variables combined have a significant positive effect at the same time on the stock price. The study recommends relying on profitability when evaluating the stock price, because the results of this study as well as the results of similar studies showed that the profitability have a significant effect on the stock price.
Keywords: Financial Analysis; Financial Ratios; Stock Price; Profitability; ROA; ROE; NPM